Free justice : a history of the public defender in twentieth-century America - Mayeux, Sara (Chapel Hill : The University of North Carolina Press, 2021)
Though often taken for granted, the modern American public defender has a surprisingly contentious history - one that offers insights not only about the 'carceral state,' but also about the contours and compromises of twentieth-century liberalism.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 5, 2021).
Keywords: Public defenders -- United States; Legal assistance to the poor -- United States; Law; Laws of specific jurisdictions & specific areas of law